INTEGRASI NILAI SOSIAL DALAM HUKUM LINGKUNGAN MODERN: PENDEKATAN SOCIO LEGAL DAN PERSPEKTIF AGAMA ISLAM - Damrah Mamang; Siti Nur Intihani; Didiet Yudhistira (Spektra: Jurnal Ilmu-ilmu Sosial, 2026)
This study explores the role of social values ​​in shaping the effectiveness of contemporary environmental law through a socio-legal approach and a theological framework. The method used is qualitative, with an emphasis on normative and conceptual analysis. The findings indicate that the success of environmental law is not solely determined by regulatory power, but also by the internalization of values ​​such as social justice, public involvement, local wisdom, and collective responsibility. In this context, an Islamic perspective provides a significant ethical foundation for maintaining ecological balance. The integration of legal norms and social values ​​results in a more responsive, inclusive, and sustainability-oriented legal model.